Complex phylogeography in Rhinoclemmys melanosterna: conflicting mitochondrial and nuclear evidence suggests past hybridization (Testudines: Geoemydidae) - Vargas-Ramírez, Mario; Carr, John L.; Fritz, Uwe (Zootaxa, 2013)
We examined differentiation within the Colombian wood turtle Rhinoclemmys melanosterna, and among R. melanosterna and the closely allied species R. diademata, R. funerea and R. punctularia, based on 1060 base pairs of the mitochondrial cyt b gene. We also assessed the phylogenetic relationships among these species using 2050 bp of mtDNA (partial cyt b, 12S and 16S genes) and 3620 bp of nuclear DNA (partial Rag 1, Rag 2, C-mos, R35 and ODC genes). There is consider-able phylogeographic structuring within R. melanosterna, with seven distinct clades distributed across the species’ range. These clades correlate to some extent with previously described differences in the dorsal pattern of head coloration. Indi-vidual and combined analyses of mitochondrial and nuclear DNA indicated contradictory relationships among R. melanosterna, R. diademata, R. funerea and R. punctularia. Mitochondrial DNA sequences revealed R. melanosterna to be non-monophyletic with respect to R. diademata, R. funerea and R. punctularia. In contrast, R. melanosterna constituted a well-supported monophyletic clade using nuclear DNA. This conflict between mitochondrial and nuclear data suggests past gene flow among the allopatrically and parapatrically distributed species R. melanosterna, R. diademata, R. funerea and R. punctularia. Compared to the other Rhinoclemmys species, the taxa under study are weakly differentiated. To assess their taxonomic status, further research is warranted using additional nuclear markers and additional samples of R. diade-mata, R. funerea and R. punctularia. For the time being, a continued classification of R. melanosterna, R. diademata, R. funerea and R. punctularia as distinct species is justified owing to their allopatric and parapatric distributions, and to con-serve the established usage of names that is based on morphological and karyotypic differentiation.